Rethinking Public Education (Revista Peruana de Investigación Educativa, 2011)
The text begins with a discussion about the concept of public education from the historical perspective since the European Illustration until the theories of the reproduction, including the contemporaneous difficulties in creating an optimistic vision of education. In Peru, the term public education was not introduced in the more democratic and modern sense, but as a way of calling education by the state, this means education for people who have no access to schools of high class children. The article shows further the existing gap between public and private education and between rural and urban education. It shows great contradictions that are adverse for everyone and require to be confronted social and politically.
Keywords: public school; access to education; democratization of education; educational discrimination; State and education